OPTIMALISASI ANGLE STUCTURAL DENGAN METODE EOQ DAN POQ PADA GALANGAN KAPAL SURABAYA - Rangga Arie Brasis Putra Pratama; Renanda Nia Rachmadita; Aditya Maharani (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2022)
The shipbuilding company at Ujung Surabaya requires raw aluminium material to carry out its operational activities. However, in 2021 the shipyard company experienced a stockout of raw aluminum material of 152 units of structural angle material, 41 units of bar metal, 31 units of elbow, 33 units of pipe, 36 units of plate metal, 28 units of raceway, and 37 units of sheet metal. This resulted in delays in procurement activities for the KCR5 project which should have been 557 days to 635 days. Therefore, the purpose of this final project is to get the optimal number of orders and purchase frequency and to get the total cost of raw material inventory that is more efficient for the company. This study uses the Economic Order Quantity (EOQ) and Periodic Order Quantity (POQ) methods to calculate the number of economic orders, safety stock, reorder points and optimal frequency, then uses the Total Annual Cost (TAC) calculation to calculate the inventory costs to be incurred. The objects in this study are 17 materials consisting of structural angle materials, pipes, plate metal, and sheet metal. The results of the study obtained the optimal number of orders, reorder points, and safety stock values to anticipate raw material shortages and obtained the total annual cost of the proposed EOQ method which could save 7,64% of the total annual cost of the company's policy.